Evaluation of Different Fluoride Concentrations Supplemented with Trimetaphosphate on Enamel De- and Remineralization in vitro - Takeshita, E. M. [UNESP]; Exterkate, R. A. M.; Delbem, Alberto Carlos Botazzo [UNESP]; ten Cate, J. M. (Karger, 2011)
Trimetaphosphate (TMP) effects on demineralized bovine enamel were studied after 15 days of pH cycling. Treatments included 30 wt% (weight percent) dilutions of 0, 500, 1,500 or 3,000 mu gF/g aqueous NaF solutions with or without 3% TMP. Treated specimens were assessed by transverse microradiography. With the exception of the 3,000 mu gF/g case, 3% TMP addition provided significant additional overall remineralization compared with F alone. Mineral content profiles differed significantly between corresponding F and F + TMP groups. Fluoride alone resulted in more remineralization in the original demineralized zone, whereas F + TMP caused less demineralization in the underlying, originally sound enamel. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Demineralization; Fluoride; pH cycling; Remineralization; Sodium trimetaphosphate